The Book review digest : Fifty-First annual cumulation ; Mar. 1955 to Feb. 1956 inclusive - James, Mrtice M.; Brown, Dorothy (New York : H.W. Wilson Co., 1956)
Book Review Digest Retrospective provides excerpts from, and citations to, reviews of adult and juvenile fiction and non-fiction. Citations with excerpts of reviews of juvenile and adult fiction and nonfiction in the English language are included. The reviews originate in a group of selected periodicals in the humanities, social sciences, and general science published in the United States, Canada, and Great Britain -- from database description.
Mode of access: World Wide Web.
Database produced by H.W. Wilson Company.
Keywords: Books -- Reviews -- Abstracts -- Databases; Books -- Reviews -- Databases